Antioxidant activity and phytochemical analysis of Clerodendrum infortunatum from Morang, Nepal (Rajarshi Janak University Research Journal, 2025)
The objective of the study was to carry out the phytochemical screening of all parts (stem, root, leaves, and flower) of Clerodendrum infortunatum, while the antioxidant assay was conducted only on flower extracts in ethanol and methanol solvents. Standard Chemical test method was used for qualitative screening of plant extracts. For the antioxidant assay, the ascorbic-iron-EDTA model was used to prepare free hydroxyl radicals (OH•). Various concentrations of floral extract (250, 500, 750, and 1000 µg/ml) were taken and treated with formulated hydroxyl radicals. The absorbance of the treated extract and control was measured at 412 nm using a UV-Vis Spectrophotometer. Antioxidant activities were determined by the calculation of % inhibition of free radicals from the absorbance value. The phytochemical screening revealed the presence of carbohydrate, alkaloid, terpenoid, flavonoid, coumarin, steroid, except glycoside and anthraquinone in all parts of the plant extract. The study also exhibited the greatest antioxidant activity with 84.58± 2.04 % of inhibition at 1000 µg/ml and IC50 at 630 µg/ml against OH• by the methanolic flower extract of Clerodendrum infortunatum, whereas the ethanolic flower extract revealed 55.12± 1.14 % of inhibition at 1000 µg/ml and IC50 at 940 µg/ml. The antioxidant activity experiment was carried out in triplicate and showed a significant (p < 0.05), concentration-dependent increase in OH• scavenging activity. The findings suggest that the flower of Clerodendrum infortunatum is a rich source of bioactive compounds. However, isolation and characterization of active phytochemicals following in-vivo validation will be an important step to verify their pharmacological potential.